Ritual Kelas pada Suku Rakas Manggarai - Urak*, Monika Putri; Saffanah, Winin Maulidya (Universitas Syiah Kuala, 2023)
The Kelas Ritual is one of the original cultures of the Manggarai community that is still conducted as a form of respect for their ancestors.